Effects of Supplementary Biofrrdback Training on Anxiety Level and Free Throw Shooting Performance In Basketball of Female Chulalongkorn University Basketball Team - Tantivorrasakulvej, Teechaya; Benjapalakorn, Benjapol (Academic Journal of Thailand National Sports University, 2018)
Purpose The purpose of this research was to study effects of supplementary biofeedback training on anxiety level and free throw shooting performance in basketball Methods Twenty membersof female Chulalongkorn University basketball teams were equally divided intoexperimental and control groups (ages average19.6 years).Participants in both groups similarly received free throw shooting training but only. The experimental group received heart rate variability biofeedback training 20 minutes a day, 3 days a week for 4 consecutive weeks. Pretest and posttest for heart rate variability, anxiety level (test with CSAI-2R) and free throw shooting accuracy in 30-seconds time limit were conducted on all participants. Means and standard deviation of the obtained data were compared using paired sample t-test for within group differences. Independent t-test was used to analyze data betweenthe experimental and control groups. Alpha level was set at p < .05. with G*Power Program Results The results showed significant-improvement of anxiety level, heart rate variability and free throw shooting accuracy (p < 0.05) in the experimental group. While only selfconfidence score was significantly increased (p < 0.05) for the control group. Furthermore, heart rate variability and free throw shooting accuracy were significantly greater inexperimental group thanincontrol group (p < 0.05), butno difference was found inanxiety level between two groups of participants. Conclusion Heart rate variability biofeedback of the experimental group could improve anxiety level, heart rate variability, heart rate while shooting and free throw shooting accuracy.